Steroid-Resistant immune thrombocytopenia: Challenges and solutions - Abhishekh Basavarajegowda; Vinod K Vishwanath; Ramamoorthy G Jaikumar; Murali Subbaiah (Journal of Applied Sciences and Clinical Practice, 2021)
Immune Thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by a platelet count of <100 × 109/L in the absence of other underlying causes of thrombocytopenia and increased risk of bleeding. Glucocorticoids are the mainstay drugs of treatment for ITP. The response rate to steroids is around 60%–70% in adults, but only 10%–15% of these patients will have a durable response. If patients do not respond to steroids by 4 weeks, they are considered to have steroid-resistant ITP. Some patients though they respond, need frequent courses of steroids to maintain a platelet count above 30 × 109/L or to avoid bleeding and are considered nonresponders to steroids. A number of potential mechanisms for this resistance to steroids have been suggested, including receptor downregulation by glucocorticoid exposure and negative inhibition by the beta-isoform of the glucocorticoid receptor. The available treatment options for these patients include various drugs including rituximab, thrombopoietin receptor agonists, fostamatinib, danazol, immunosuppressive drugs, and biological therapies including intravenous immunoglobulin, Rh immunoglobulins, and immunoadsorption. Splenectomy has been performed surgically, by radiation, or chemoembolization. Supportive treatment includes screening for osteoporosis and management, vaccination, and platelet therapy. Newer therapies such as veltuzumab, belimumab, and toralizumab which deplete B-cells have been tried. Nearly 70% of adult chronic ITP patients failing to respond to splenectomy still achieve stable remission with additional therapies.